The predictors of necrotizing enterocolitis in newborns with low birth weight: A retrospective analysis. Issue 7 (18th February 2022) - Tan, Xuerong; Zhou, Yunxia; Xu, Lan; Zhang, Li; Wang, Jiaying; Yang, Wenqiong
Abstract : Abstract: There are needs to investigate the influencing factors of necrotizing enterocolitis (NEC) in low birth weight (LBW) newborns, to provide insights into the clinical management of NEC. This study was a retrospective cohort study. Infants admitted to our hospital from January 1, 2019 to June 30, 2021 were selected. The clinical characteristics of NEC and no-NEC infants were evaluated. Logistic regression analyses were conducted to assess the risk factors of NEC in LBW infants. A total of 192 LBW infants were included, the incidence of NEC in LBW infants was 35.42%. There were significant differences in the congenital heart disease, sepsis, breastfeeding, blood transfusion and probiotics feeding between NEC and no-NEC group (all P < .05), and there were no significant differences in birth weight, gestational age, mother's pregnancy-induced hypertension, premature rupture of fetal membrane, amniotic fluid pollution, fetal asphyxia, neonatal respiratory distress syndrome and mechanical ventilation between NEC and no-NEC group (all P > .05). Congenital heart disease (OR: 2.128, 95% CI: 1.103–3.511), sepsis (OR: 1.630, 95% CI: 1.022–2.549), and blood transfusion (OR: 1.451, 95% CI: 1.014–2.085) were the independent risk factors for NEC in LBW infants, and breastfeeding (OR: 0.494, 95% CI: 0.023–0.928), probiotics feeding (OR: 0.816, 95% CI: 0.782–0.982) were the protective factors for the NEC in LBW infants. The prognosis of NEC infants undergone surgery treatment was better than that of infants undergone conservative treatments ( P = .043). The incidence of NEC in LBW is high, which is affected by many factors, and comprehensive interventions targeted on the risk and protective factors should be made to improve the prognosis of LBW infants.